Gestational Malaria and Living Conditions in Turbo, Colombia - Jaime Carmona-Fonseca; María Mercedes Arias V.; Adriana Correa B.; Maritza Lemos C. (Social Medicine Publication Group, 2011)
Background: The study of gestational malaria has focused on biomedical aspects and ignored social aspects. Objectives: To describe the socio-economic characteristics of families with and without gestational malaria in Turbo (Antioquia, Colombia). Methodology: Descriptive study using socio-economic surveys in a random sample of 84 mothers/families. Results: There was no statistically significant differences between pregnant women with and without gestational malaria in terms of the characteristics examined. The mothers were between ages 23 ±5 years, 64% of peasant origin, 14% illiterate, 61% educated to primary school level, 17% with knowledge of a particular trade. Among the 23 % of mothers doing paid work it was marginal work in all cases; 63% were direct operators and 37% were administrators/managers; average monthly income 166,000 pesos (USD $83). Spouses/partners worked as follows: 52% miscellaneous occupations, 17% in farming; average monthly income 320,000 pesos (USD $160). Complete nuclear families were found in 77% of cases and averaged 5.4 members each. Housing: 63% family owned; 2.5 sleepers/room; 2.5 sleepers/mosquito net. There was no anti-mosquito activity in 62% of families. Drinking/cooking water: 76% use rainfall as sole or combined source. Connection to sewage system: 59%. Home environment: 71% with vegetation and flowing/stagnant water. Waste: 26% dumped on the ground/in the water. Conclusions: The living conditions of these families are less than satisfactory. Mothers are financially dependent (80%) and those with paid employment (20%) work in marginal activities. The home environment and families' antimalarial practices strongly favor the presence of malaria.